A case study on BHP Steel (Malaysia) Sdn. Bhd - Hassan, Haslina (2001)
BHP Steel (Malaysia) Sdn Bhd (BSM) was a joint venture company between BHP Steel (JLA) Pty Ltd (BHP) and PNB Equity Resource Corporation Sdn Bhd (PERC). The joint venture agreement with PERC, a wholly owned subsidiary company of Permodalan Nasional Berhad (PNB) was signed on 13th June 1995, with an authorized capital or RM200 million. The issued paid up capital is RM100 million. BSM was 60% owned by BHP and 40% owned by PERC. Though new in this industry, BSM has managed to put themselves as one of the key players in construction industry. This is due to BSM is one of the subsidiaries for BHP Steel Pty (JLA) Australia. Orders intake for past few years has been quite good but lately it seem the orders has been on the reducing trend. Complaints from customers have increased and customers have voice out their unhappiness openly. Result from Customers' Satisfaction survey confirmed that they are not happy with current process and the way they have been treated by BSM's employee. They have commented though technology and quality are important factors in the product, delivery and good service plays equal importance on ensuring BSM retain its customers. The have identified possibilities that cause the delays: 1. Too many steps involved in doing simple task. Some processes maybe obsolete and redundant and can do without. 2. Every department is task-oriented, and they only know what happened in their respective department. 3. Too many manual documents for generating sales contract, shop floor paper, delivery note and invoice. Tendency to miss-out or wrong information keyed-in in the documents and timely checking and reconciliation. 4. No in-depth knowledge in SAP and its function. Incompetent of the employee to perform certain task resulted to wrong order entered in the system, missed order, wrong scheduling, wrong order and product produced, wrong delivery and late in billing. Due to this, the management has decided to review the process and map the process to find out the loop-hole. Thus, reengineering process is one of the options that can help to review the systems. Reengineering mean abandoning long-established procedures and looking a fresh as the work required creating a company's product and services and delivering the value to the customer. It also means tossing aside old system and starting over. It involves going back to the beginning and inventing a better way of doin gwork. The formal definition of reengineering is "the fundamental rethinking and radical redesign of business processes to bring dramatic changes and improvements in performance". In implementing the reengineering process, it involves the leader, the process owner, the reengineering team and czar. And each party must know their function to ensure the sooth running of the reengineering. The failure of the reengineering is very much dependent on a few factors such as people, process and tools. It is important to ensure that people or employees understand why or the objective of reengineering. As the successful of the reengineering process depend on the willingness of th emeployees accepting changes. Commitment from top management is equally important and they clear vision of the direction of how the new process should work. This include committed to the implementation of the processes. The management has to cultivate the corporate culture for the people to participate in the reengineering and in line with the new mission and objective of the company. From the reengineering process, the management has managed to identify redundant and obsolete tasks that can do without. Process and activities has reduced tremendously and have becom more customer-focus. However, reengineering need more than mapping the process. It involves good information technology, constant follow-up and more importantly the readiness and willingness of the employees to change and accept new changes.